Diversity of the ichthyofauna in the Serra do Mar State Park- Núcleo Santa Virgínia, Sáo Paulo State, Brazil - Gomiero, Leandro Muller [UNESP]; Braga, Francisco Manoel de Souza [UNESP] (Universidade Estadual de Maringa, 2006)
The aim of this work was to assess and compare the diversity of the ichthyofauna in three headwater rivers of Paraíba-do-Sul basin in the Serra do Mar State Park, Núcleo Santa Virgínia. A total of 1,774 specimens of 16 species of fishes belonging to 6 families were caught. Characiforms were the most abundant fish at all three sites, followed by Cyprinodontiformes, Siluriformes, and Perciformes. The Shannon index (H′), evenness (E), and the Jaccard and Morisita-Horn similarity indexes were low, indicating both low diversity and low similarity of species among the three streams. The values of these indexes should be evaluated according to the biotic and abiotic conditions in each environment. It is clear that in mountain streams of the Atlantic Forest, these low values occur because of the presence of a few abundant and many rare species.
Keywords: Atlantic Forest; Brazil; Diversity; Fish; Similarity; aquatic environment; aquatic species; controlled study; fish; nonhuman; species diversity; Characiformes; Cyprinodontiformes; Perciformes; Pisces; Siluriformes